2002
DOI: 10.1046/j.1464-4096.2001.02418.x
|View full text |Cite
|
Sign up to set email alerts
|

Antegrade scrotal sclerotherapy in the treatment of varicocele: a prospective study

Abstract: Results The mean operative duration was 15 min; there were no signi®cant complications during treatment and all patients were discharged within 4 h. Complications after treatment occurred in 10 of the 201 patients (5%); four patients had epididymoorchitis, three a scrotal haematoma, one a surgical wound infection, one persistent scrotal pain and one persistent¯ank pain on the same side as the surgery. Re¯ux was persistent in 12 patients (6%). Conclusions Antegrade scrotal sclerotherapy is a simple, minimally i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 25 publications
2
31
0
4
Order By: Relevance
“…Several studies have reported this to have a better diagnostic accuracy than physical examination, with the most widely accepted criteria for diagnosis being the presence of multiple veins greater than 3.0-3.5 mm in diameter with reversal of flow on Valsalva [6] . Spermatic venography is the "gold standard" for diagnosis but is primarily employed during intended treatment of varicocele, be it surgical or percutaneous [6,[9][10][11][12] . Reflux that lasts at least two seconds has been reported as equivalent to a positive venography result [1] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported this to have a better diagnostic accuracy than physical examination, with the most widely accepted criteria for diagnosis being the presence of multiple veins greater than 3.0-3.5 mm in diameter with reversal of flow on Valsalva [6] . Spermatic venography is the "gold standard" for diagnosis but is primarily employed during intended treatment of varicocele, be it surgical or percutaneous [6,[9][10][11][12] . Reflux that lasts at least two seconds has been reported as equivalent to a positive venography result [1] .…”
Section: Discussionmentioning
confidence: 99%
“…Venography following surgical cannulation of a vein of the pampiniform plexus has been well described in the urology literature [9][10][11][12]17,18] , but is infrequently referred to in the radiology literature. In addition, there is little mention of the anatomy that is appreciated through venography by this route.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the end atoxysclerol mixed with air is injected. [2][3][4][5] This technique is well-established to treat varicocele. It is easier, faster and less invasive than open surgical and laparoscopic treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In the search for less traumatic treatment approaches, minimally invasive techniques such as laparoscopic varicocelectomy (LV), antegrade sclerotherapy (AS), and retrograde embolization (RE) were developed and have gained popularity during the last decade. A number of reports on these techniques used to treat series of pediatric or adult patients with varicoceles are available in the literature [1,7,12,19,21,22,25]. However, to our knowledge, no published study has evaluated the efficacy and complications of several minimally invasive procedures and their outcomes comparing the findings for children and adolescents with those for adults treated in the same institution.…”
mentioning
confidence: 99%